Matched template analysis of continuous wave laser for space debris ranging application. Issue 7 (1st October 2022) - Raj, Shasidran; Francis, Samuel; Roberts, Lyle; Ward, Robert; McClelland, David; Shaddock, Daniel
Abstract: The growth of human-made space debris, sharing the same Earth's orbital space as active satellites, is a worrying environmental condition. Precise tracking and orbital modelling of space debris are vital to predict potential future collisions with active satellites. This paper investigates a continuous-wave laser ranging method where a bench-top experiment models the reflected amplitude modulated optical signal from a space debris target. The optical signal is digitised and stored to undergo post-digital signal processing using a parameter estimation matched filter approach to estimate the time-varying delay between the target debris and the observing telescope. The experiment investigated two different detection methods, the direct detection of the optical signal and the coherent detection where the optical signal is amplified with a bright local oscillator before signal detection. The experimental results show that the coherent detection method can provide a more precise time-varying delay estimate than the direct detection method due to the improved signal-to-noise ratio. The experimental results also show improved precision in the parameter estimation when using larger portions of the acquired signal's time series. The experimental results were used to model for a potential space debris application. For example, assuming the received signal power from the target debris is approximately 3.5 fW, the time-varying delay of the target debris using the coherent detection method can be estimated with a precision of 1 m / s using 2.5 s of the acquired signal time series. This is well within the expected minimum time series that can be collected from a space debris target from a single flyover at the telescope site.